Lo splendore orientale: la collezione Wurts di arte asiatica - Pollard, C (Arte'm, 2017)
An exploration of the Japanese objects in the collections of Rome-based American collectors George and Henriette Wurts, within the context of the Japanese art collecting in Italy in the late 19th century. Accompanied by detailed catalogue entries of ten objects from the collection.